1987
DOI: 10.1177/002199838702100703
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Carbon/Epoxy Lamina Under Combined Stress

Abstract: It is well known that matrix failure in carbon/epoxy composites is influenced by multiaxial states of stress. However most of the experimental work to measure this interaction has not focused exclusively on matrix failure, and a general multiaxial stress criterion for matrix failure has not been established. To examine this question experimentally we have carried out a series of tests involving torsional shear combined with axial tension or compression of unidirectional hoop wound cylinders, using AS4/55A carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 18 publications
4
50
0
Order By: Relevance
“…The assumption that fiber-direction tensile failure is controlled by the fiber quantities is support by Swanson and co-workers (Swanson et al, 1987). They performed bi-axial testing on several carb0n-fiber uni-directional composites, and concluded that e~l/does not vary with physically achievable bi-axial loads -including shear.…”
Section: = + Vmomentioning
confidence: 93%
“…The assumption that fiber-direction tensile failure is controlled by the fiber quantities is support by Swanson and co-workers (Swanson et al, 1987). They performed bi-axial testing on several carb0n-fiber uni-directional composites, and concluded that e~l/does not vary with physically achievable bi-axial loads -including shear.…”
Section: = + Vmomentioning
confidence: 93%
“…The criterion adequately accounts for this trend. The second example-not a part of the WWFE tasksapplied additional multi-axial loading to tubular specimens so as to determine failure data for AS4/55A (Swanson et al 1987) whose properties were similar to the AS4/3501-6 carbon fiber. The resin property needed to be adjusted to match the replacement resin.…”
Section: Lamina Failure Under Combined σ Y and τ X Ymentioning
confidence: 99%
“…4 Figure 6. Combined longitudinal shear and transverse compression failure envelopes E-Glass/LY556, 18 T800/3900-2 19 and AS4/55A 20 .…”
Section: Combined Longitudinal Shear and Transverse Loadingmentioning
confidence: 99%